Quantitative HBsAg and HBeAg Predict Hepatitis B Seroconversion after Initiation of HAART in HIV-HBV Coinfected Individuals - Matthews, Gail V. (Public Library of Science, 2013)
OBJECTIVE: Anti-HBe seroconversion and HBsAg loss are important therapeutic endpoints in patients with hepatitis B virus (HBV) infection. Quantitative measures of hepatitis B surface antigen (qHBsAg) and e antigen (qHBeAg) have been identified as potentially useful indicators of therapeutic response in HBV monoinfection. The aim of this study was to examine serological change including quantitative biomarkers in HIV-HBV coinfected patients initiating HBV active antiretroviral therapy (ART). METHODS: HIV-HBV coinfected individuals from Thailand were followed for up to 168 weeks post ART. Rates and associations of qualitative serological change were determined. Longitudinal changes in qHBsAg and qHBeAg were measured and their utility as predictors of response examined. RESULTS: Forty seven patients were included of whom 27 (57%) were HBeAg positive at baseline. Median CD4 count was 48 cells/mm(3). Over a median follow-up of 108 weeks 48% (13/27) lost HBeAg, 12/27 (44%) achieved anti-HBe seroconversion and 13% (6/47) HBsAg loss. Anti-HBe seroconversion was associated with higher baseline ALT (p = 0.034), lower qHBsAg (p = 0.015), lower qHBeAg (p = 0.031) and greater HBV DNA decline to week 24 (p = 0.045). Sensitivity and specificity for qHBsAg and qHBeAg decline of >0.5 log at week 12 and >1.0 log at week 24 were high for both anti-HBe seroconversion and HBsAg loss. CONCLUSIONS: Rates of serological change in these HIV-HBV coinfected individuals with advanced immunodeficiency initiating HBV-active ART were high. Baseline and on treatment factors were identified that were associated with a greater likelihood of subsequent anti-HBe seroconversion, including both quantitative HBsAg and HBeAg, suggesting these biomarkers may have utility in this clinical setting.